1996
DOI: 10.1084/jem.184.2.579
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 inhibits tumor metastasis through an NK cell-dependent mechanism.

Abstract: SummaryInterleukin-10 (IL-10) is a recently described pteiotropic cytokine secreted mainly by type 2 helper T cells. Previous studies have shown that IL-t0 suppresses cytokine expression by natural killer (NK) and type 1 T cells, thus down-regulating cell-mediated immunity and stimulating humoral responses. We here report that injected IL-t0 protein is an efficient inhibitor of tumor metastasis in experimental (B16-F10) and spontaneous (M27 and Lox human melanoma) metastasis models in vivo at doses that do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
144
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 34 publications
5
144
1
Order By: Relevance
“…These findings indicate that decreased expression of IL-10 in tumor destroys antitumor mechanisms and causes progression of the disease. In support of this hypothesis, some studies have shown that systematic prescription of IL-10 prevents metastasis in melanoma tumor cells, sarcoma and colorectal cancer (Berman et al,1996;Zheng et al,1996).…”
Section: Discussionmentioning
confidence: 92%
“…These findings indicate that decreased expression of IL-10 in tumor destroys antitumor mechanisms and causes progression of the disease. In support of this hypothesis, some studies have shown that systematic prescription of IL-10 prevents metastasis in melanoma tumor cells, sarcoma and colorectal cancer (Berman et al,1996;Zheng et al,1996).…”
Section: Discussionmentioning
confidence: 92%
“…Traditionally, Th1 have been thought to be associated with cellmediated immunity and Th2 to be related to humoral immunity. However, both types of T cells have been shown to participate in the antitumor immune response (37)(38)(39)(40)(41)(42). The heterogeneity of cytokine profiles has been extensively demonstrated (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…22 Parallel depletion studies performed with B16 cells showed no involvement of T cells confirming previous evidence indicating that NK cells were mainly responsible for tumor rejection in the B16 melanoma model. 13 The involvement of either NK or T cell subset in an antitumor response was suggested to be related to MHC class I expression by the tumor cells. Down-regulation of MHC class I levels was associated with increased NK activity.…”
Section: Discussionmentioning
confidence: 99%